PENERAPAN STRATEGI PEMBELAJARAN AKTIF KARTU SORTIR UNTUK MENINGKATKAN HASIL BELAJAR KIMIA SISWA DI SMA NEGERI 2 TANJUNG RAJA - Yulizar, Yulizar (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Tthis research to enhance student?s learning outcomes in Chemistry subject of XI MIA 3 of SMA Negeri 2 Tanjung Raja through the application of active learning strategies with sorting cards. This research was conducted at SMAN 2 Tanjung Raja with the sample of this research was XI MIA 3 totaling 28 students consisting of 12 male and 16 female. This research was conducted in three cycles that consist of two meetings on each cycle. The data collection was done through the test at the final stage on each cycle and observation along the learning process. The students average score before treatment (T0) was 60.18 with the percentage range was 28.57%. Based on the results of this research, the student average score in the first cycle (T1) was 74.73 with the percentage range of 46.43%. Students became interested and motivated in the learning process, but have not yet reached complete learn, because there was still weaknesses as students who are not active in seeking friends that one category and students who are not active in making presentations. In the second cycle (T2), the student average score was 77.71 with the percentage range was 69.23%. The students scoring at the second cycle was higher than the first cycle, because on the second cycle which students were required to read first, understand the material and do the exercises. But has not reached indicators of mastery learning, there was students who are not active in making the presentation material and exercises. In the third cycle (T3), the student average score was 85.48 with the percentage range was of 85.19%. The students scoring in the third cycle was higher than the score of the second cycle, because in the third cycle which students record and understand the results of the exercises were done, then the third cycle indicator value has reached mastery learning. In conclusion, result of this research showed that the application of active learning strategies with sorting cards has improved students learning outcome in chemistry.